2009
DOI: 10.1200/jco.2008.18.0463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FcγRIIa-FcγRIIIa Polymorphisms and KRAS Mutations on the Clinical Outcome of Patients With Metastatic Colorectal Cancer Treated With Cetuximab Plus Irinotecan

Abstract: Combined FcgammaRIIa/FcgammaRIIIa polymorphisms are prognostic factors for disease progression in mCRC patients treated with cetuximab plus irinotecan. As these polymorphisms are also clinically relevant in mutated-KRAS mCRC, an important role of ADCC in cetuximab efficacy is presumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
333
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(362 citation statements)
references
References 41 publications
19
333
2
4
Order By: Relevance
“…Consistent with the mechanisms of action for antibodies used to target cell-surface molecules in B-cell malignancies and in solid tumors (29)(30)(31)(32), ADCC mediated by NK cells was found to be an important mode of action for killing of human AML cells. In contrast, neither of the anti-IL1RAP antibodies mediated specific cell death by ADCP or CDC of MA9Ras cells in vitro, suggesting that these mechanisms may be less critical for the observed effects.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with the mechanisms of action for antibodies used to target cell-surface molecules in B-cell malignancies and in solid tumors (29)(30)(31)(32), ADCC mediated by NK cells was found to be an important mode of action for killing of human AML cells. In contrast, neither of the anti-IL1RAP antibodies mediated specific cell death by ADCP or CDC of MA9Ras cells in vitro, suggesting that these mechanisms may be less critical for the observed effects.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, in some cases, patients bearing the higher affinity Fc␥RIIa polymorphism, His 131 , have improved clinical responses to bacterial infections (69) and improved IgG2-mediated phagocytosis of opsonized bacteria (70). These correlations between higher affinity Fc␥R-mAb interactions and efficacy are also in line with the observation that in some cases patients bearing higher affinity Fc receptor polymorphisms have a more favorable clinical response to IgG1 mAb-mediated cancer therapies (71)(72)(73). For these reasons, one common goal for Fc engineering efforts is to generate Fc variants that demonstrate improved effector functions in patients bearing lower affinity Fc␥R polymorphisms (35,74).…”
Section: Discussionmentioning
confidence: 67%
“…Further studies have consolidated these findings and, in addition, have demonstrated the importance of an additional polymorphism, FcgRIIA 131H/H (Weng and Levy, 2003), although the mechanism by which this polymorphism achieves superior engagement is not yet fully defined, as it does not show differential IgG1 affinity (Desjarlais et al, 2007). More recently, data relating to the prognostic significance of these polymorphisms in response to other antibodies, including trastuzumab (Musolino et al, 2008) and cetuximab (Bibeau et al, 2009), have been reported, which indicate similar trends. However, it should be noted that such data are not without controversy.…”
Section: Data Supporting the Role Of Fc-mediated Mechanisms In Antibomentioning
confidence: 63%
“…This will inform a variety of strategies aimed at maximising patient response, including genotyping patients to predict response and development of next-generation antibodies, which achieve efficacy irrespective of Fc-receptor polymorphism status. Such analysis may be confounded by other, independent factors that influence responses to targeting functional tumour antigens, for example, PI3-kinase mutation status in trastuzumab therapy (Junttila et al, 2009) and K-ras mutation status in cetuximab treatment (Bibeau et al, 2009). …”
Section: Data Supporting the Role Of Fc-mediated Mechanisms In Antibomentioning
confidence: 99%